From passive consumption of media goods to active use of media brands: on value generation and other differences (Communication & Society, 2019)
Analyses of business models and media consumption within the traditions of media economics and media management explicitly –but mostly implicitly– rely on the representation of a media consumer that rationally pursues the maximisation of utility. Such concept provides the basis for the generalised understanding of the passive consumer of media goods, motivated by subjective wants, needs and preferences. Yet, the digitalisation of media production and distribution has fundamentally changed consumers, producers and their relationship. Users of digital media platforms select, purchase or attend the output of media providers, and leave traces of their digital activities for marketers and advertisers. In addition, they supply content, rate, comment, and share or promote among their network the offers of media providers. The increasing variety of media providers are better understood as brands proposing different value generating activities rather than substitute products at different prices. Critically and by drawing from literature from a variety of research traditions, including political economy of communication, sociology, philosophy and marketing, this theoretical paper discusses the features of the active user of media brands, the hypothetical recipient of the business models of digital media services such as YouTube, Google, Netflix, Amazon Video or Facebook. It is argued that practical knowledge, affect, different types of gratifications and universal values, which are guiding principles for a better life, should be taken into account